The Effect of Communication, Work Facilities, and Service Speed on Community Satisfaction at Bengkong Sadai Village Office, Batam City - Sari, Devita Leila; Sumardin, Sumardin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to to analyze the effect of communication, work facilities, and service speed on community satisfaction at the Bengkong Sadai Village Office, Batam City. Public service institutions are expected to provide effective, responsive, and citizen-oriented services to ensure positive perceptions from the community. In the context of village administration services, the quality of communication between officers and citizens, the adequacy of work facilities, and the speed of service delivery become critical factors influencing public satisfaction. Understanding how these variables shape community perceptions is important for improving service quality and strengthening public trust in local government institutions. Materials and methods. This research employed a quantitative explanatory approach with a survey method. The population consisted of 48,695 residents who had received services from the Bengkong Sadai Village Office. Using the Slovin formula with a 10% margin of error, a sample of 100 respondents was obtained. Data were collected using a structured questionnaire measured on a five-point Likert scale. Prior to hypothesis testing, the research instrument was evaluated through validity and reliability tests to ensure measurement accuracy and internal consistency. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to ensure the suitability of the regression model. Multiple linear regression analysis was then applied to test the research hypotheses using t-tests, F-tests, and the coefficient of determination (R²). Results. The findings reveal that communication (Sig.=0.029), work facilities (Sig.=0.032), and service speed (Sig.=0.041) each have a positive and significant effect on community satisfaction. These results indicate that clear information delivery, adequate service facilities, and efficient service processes contribute significantly to improving citizens’ satisfaction with public services. Simultaneously, the three variables significantly influence community satisfaction (F-test Sig.=0.000). The regression model demonstrates a strong relationship (R=0.743) with an explanatory power of 55.2% (R²=0.552; Adjusted R²=0.538), indicating that more than half of the variation in community satisfaction can be explained by the variables examined in this study. Conclusions. Community satisfaction at the Bengkong Sadai Village Office is significantly influenced by the combined role of effective communication, adequate work facilities, and responsive service delivery. Improving these aspects in an integrated manner can strengthen the quality of public services and enhance citizens’ confidence in administrative institutions. Strengthening communication practices, improving service facilities, and ensuring efficient service procedures are therefore essential strategies for increasing public satisfaction and supporting sustainable improvements in local government service performance.